2011
DOI: 10.3168/jds.2010-3421
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of heat stress on milk yield of Thai Holstein crossbreds

Abstract: The threshold for heat stress on milk yield of Holstein crossbreds under climatic conditions in Thailand was investigated, and genetic effects of heat stress on milk yield were estimated. Data included 400,738 test-day milk yield records for the first 3 parities from 25,609 Thai crossbred Holsteins between 1990 and 2008. Mean test-day milk yield ranged from 12.6 kg for cows with <87.5% Holstein genetics to 14.4 kg for cows with ≥93.7% Holstein genetics. Daily temperature and humidity data from 26 provincial we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 16 publications
(19 reference statements)
6
60
0
2
Order By: Relevance
“…These results are in agreement with other studies that have reported CORT decrease some days after heat stress imposition (Collier et al 2008;Boonkum et al 2011). The total amount of CORT released during the present study confirmed that CORT was significantly higher during heat stress than comfort and ACTH tests; this indicated that heat stress is a potent stressor.…”
Section: Time Sampling Datasupporting
confidence: 83%
“…These results are in agreement with other studies that have reported CORT decrease some days after heat stress imposition (Collier et al 2008;Boonkum et al 2011). The total amount of CORT released during the present study confirmed that CORT was significantly higher during heat stress than comfort and ACTH tests; this indicated that heat stress is a potent stressor.…”
Section: Time Sampling Datasupporting
confidence: 83%
“…These results implied that upgrading dairy cows to H under these Thai environmental conditions was favorable for milk production but unfavorable in terms of mastitis resistance and health status. Among Thai H crossbreds, cows with high H fraction were found to have higher levels of heat stress especially cows with more than 93.7% H fraction (Boonkum et al, 2011). In order to achieve or maintain high levels of milk production under Thai tropical environmental conditions, H cows and cows with high H fractions would need more intensive care and management (feeding, housing, milking, health care) than cows with lower H fractions (Koonawootrittriron et al, 2009; Boonkum et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the dairy cows are crossbred from Bos indicus , such as Sahiwal, Brahman and Thai Native cattle upgraded by HF (Boonkum et al . ). Currently, the majority of the dairy population has >75% HF blood.…”
Section: Methodsmentioning
confidence: 97%